Microlearning in forming the students' english competencies with VR involvement - Fedorova, Olha; Shumskyi, Oleksandr; Golikova, Oksana; Kutsenko, Iryna; Serdiuk, Nataliia; Zahorodna, Oksana (LUMEN Publishing House, 2022)
Every year the problem of higher educational establishments’ modernization, introduction of the newest methods and strategies of educational process reorganization, estimation of achievements in the context of information technologies becomes more and more urgent. The situation with the COVID-2019 pandemic has demonstrated the need to involve additional information approaches to teaching within the system of blended learning in higher educational establishments. As a result, the question arises: what mechanisms can be used to make learning effective? The article reveals the concept of “microlearning” as the latest approach in education and identifies its key tools in formation of English-language competencies in university students. The study found that microlearning can be an effective complement to traditional learning, as it extends the learning process beyond the classroom on the basis of information technology, allows consolidating virtually and deepening the knowledge gained during practical classes, and provokes students to daily communication outside the establishment through social network. Moreover, we propose a strategy for implementation of microlearning on the example of the educational process at Kherson State Maritime Academy through interaction of practical classes in the line of communicative-competency approach, virtual and online learning on the principle of rotation.
Keywords: microlearning; learning management system; online learning; computer training module; virtual reality; communicative-competency approach